STUDENTS’ VIEWS ON LITERATURE-BASED LEARNING MODEL IN OPTIMIZING ENGLISH SKILLS (Proceedings of English Linguistics and Literature, 2022)
The use of literature in language learning effectively improves students' language skills. It is because literature consists of various works such as prose, drama, and poetry that can be used as a source of extensive reading material. Therefore, using literary works for learning model trains students’ receptive skills (reading) and their productive skills (speaking). This research aims to investigate students’ views on the use of literature in English learning activities. The participants of this research are 6th semester students of the English language education department at Sekolah Keguruan Ilmu Pendidikan (SKIP) Yayasan Pendidikan Ujung Pandang (YPUP), with a total of 17 participants. To answer the research questions, the researchers used an exploratory case study, which employs qualitative research methods to collect data. The researchers utilized a research instrument called the self-assessment survey. Based on the results of students’ views on literature-based learning model, it shows that using literature in English learning is effective for language skills development. Moreover, the use of literature also provides cultural understanding, which makes students tolerate and respect the diverse cultures of others.